Genomic insights into the sessile life and biofouling of barnacles (Crustacea: Cirripedia) - Jack Chi-Ho Ip; Jian-Wen Qiu; Benny K.K. Chan (Heliyon, 2021)
Members of the infraclass Cirripedia, commonly called barnacles, are unique among the subphylum Crustacea in that they exhibit a biphasic life cycle with a planktonic larval stage and a sessile adult stage. Understanding their unique sessile life and mechanisms of attachment are hampered by the lack of genomic resources. Here, we present a 746 Mb genome assembly of Lepas anserifera – the first sequenced stalked barnacle genome. We estimate that Cirripedia first arose ~495 million years ago (MYA) and further diversified since Mesozoic. A demographic analysis revealed remarkable population changes of the barnacle in relation to sea-level fluctuations in the last 2 MYA. Comparative genomic analyses revealed the expansion of a number of developmental related genes families in barnacle genomes, such as Br–C, PCP20 and Lola, which are potentially important for the evolution of metamorphosis, cuticle development and central nervous system. Phylogenetic analysis and tissue expression profiling showed the possible roles of gene duplication, functional diversification and co-option in shaping the genomic evolution of barnacles. Overall, our study provides not only a valuable draft genome for comparative genomic analysis of crustacean evolution, but also facilitates studies of biofouling control.